The Distributional Impact of the Fiscal System in Albania - Davalos, Maria E.; Robayo-Abril, Monica; Shehaj, Esmeralda; Gjika, Aida (World Bank, Washington, DC, 2018)
In a context of fiscal consolidation and the need to deliver on a structural reform agenda, policy makers in Albania must not lose sight of the critical redistributive role of the fiscal system, particularly its impact on poverty and inequality. Using household survey data, this paper estimates the redistributive effect of fiscal policy on income distribution and poverty in Albania, assessing the individual and combined effects of taxes and public social spending. The findings show that the fiscal system in Albania plays a positive role in reducing inequality. Yet, it has a moderate poverty-increasing effect. Specifically, taxes and social protection contributions have a poverty-increasing effect; indirect taxes, particularly the value-added tax, account for the largest increases in poverty. This effect is somewhat compensated by direct government transfers, which are pro-poor and equalizing, but are not large enough to offset fully the negative impact on the taxation side. Ongoing reforms aimed at improving the efficiency and targeting of social assistance can contribute to enhancing the pro-poor impact of the fiscal system.